Sewage Sludge Recycling and Disposal - Nor Azalina, Rosli; Hamidi, Abdul Aziz; Mohamad Razip, Selamat; Lim, Leonard Lik Pueh; Hung, Yung Tse (Springer Nature, 2022)
This chapter introduces the potential recycling of sewage sludge in landfll cover application. The subtopic includes the generation and properties of sewage sludge as well as the current practices on sludge handling, treatment, and management. Since 2000, the recycling of sewage sludge has gained interest around the world in order to manage the sludge sustainably and economically. Nevertheless, sludge modifcation is required to stabilize and enhance the mechanical and geotechnical performance of the sludge. The leaching behavior was also studied in order to address the short- and long-term environmental effects of using the modifed sludge for various applications.